2018
DOI: 10.1155/2018/6962439
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Polysaccharides Isolated from Dendrobium officinale against Acetaminophen‐Induced Liver Injury in Mice via Regulation of the Nrf2‐Keap1 Signaling Pathway

Abstract: The effect of polysaccharides isolated from Dendrobium officinale (DOP) on acetaminophen- (APAP-) induced hepatotoxicity and the underlying mechanisms involved are investigated. Male Institute of Cancer Research (ICR) mice were randomly assigned to six groups: (1) control, (2) vehicle (APAP, 230 mg/kg), (3) N-acetylcysteine (100 mg/kg), (4) 50 mg/kg DOP, (5) 100 mg/kg DOP, and (6) 200 mg/kg DOP. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in the serum and glutathione (GSH), malon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 49 publications
(52 reference statements)
2
29
0
Order By: Relevance
“…The change in ROS expression is consistent. The same result is found in other studies (55, 56). In addition, significant upregulation of HO-1 expression occurred in BZE + APAP-treated cells.…”
Section: Discussionsupporting
confidence: 92%
“…The change in ROS expression is consistent. The same result is found in other studies (55, 56). In addition, significant upregulation of HO-1 expression occurred in BZE + APAP-treated cells.…”
Section: Discussionsupporting
confidence: 92%
“…Nrf2 also has a crucial role in maintaining cellular redox homeostasis that allows adaptation and survival against mitochondrial damage and cell death. HO-1/Nrf2 signals have potentials to avoid the drug-induced hepatocellular injury [32]. In this study, we showed that SAC stimulated the expression of HO-1 and Nrf2 proteins by reducing oxidative damage and regulating antioxidative enzymes to protect against APAP-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 70%
“…Oxidative stress is highly correlated with APAP-induced hepatotoxicity that promotes ROS and NO overproduction because APAP-induced acute liver failure reduced antioxidant enzyme expression [31]. SOD, CAT, and GPx are antioxidant enzymes protecting cells from oxidative stress [32]. The Nrf2/Keap1 pathway is a key cellular defense mechanism that plays a key role in the regulation of phase II detoxifying and antioxidant enzymes in preventing APAP-induced acute liver failure [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chinese medicine theory, (Bulpitt, 2007 #502; Yu, 2018 #503) D. officinale clears heat and nourishes the lung, thereby treating lung-related diseases and improving the overall life quality of patients with lung cancer [29]. In modern pharmacological studies, (Bulpitt, 2007 #502; Yu, 2018 #503) D. officinale has displayed significant bio-active functions, including immunomodulatory [30,31], antioxidant [32,33], anti-inflammatory [34], antitumor [35,36] and hepatoprotective functions [37]. To date, most of the research in this area has been focused on polysaccharides and extracts from (Bulpitt, 2007 #502; Yu, 2018 #503) D. officinale , but flavonoids are a widespread group of significant substances with various biological pharmacological functions [38].…”
Section: Introductionmentioning
confidence: 99%